Interpreting the outsider tradition in British European policy speeches from Thatcher to Cameron - Daddow, Oliver J. (Wiley, 2015)
This article investigates how British European policy thinking has been informed by what it identifies as an ‘outsider’ tradition of thinking about ‘Europe’ in British foreign policy dating from imperial times to the present. The article begins by delineating five phases in the evolution of the outsider tradition back to 1815 through a survey of the relevant historiography. The article then examines how prime ministers from Margaret Thatcher to David Cameron have looked to various inflections of the outsider tradition to inform their European discourses. The focus in the speech data sections is on British identity, history and the realist appreciation of international politics that informed the leaders' suggestions for EEC/EU reform. The central argument is that historically informed narratives such as those making up the outsider tradition do not determine opinion-formers' outlooks, but that they can be deeply impervious to rapid change. We can therefore understand why Britain has come to hover near the EU exit door because British leaders have consistently drawn upon ‘outsider’ narratives as the organizing frame for their European policy discourses.